Communicative deficits associated with maladaptive behavior in individuals with deafness and special needs - Fellinger, Johannes; Dall, Magdalena; Weber, Christoph; Holzinger, Daniel (Frontiers in Psychiatry, 2022)
Background: At least one in three individuals who are prelingually deaf has special needs, most commonly due to intellectual disabilities. The scant literature on challenging behavior in this population, however, suggests high rates of prevalence and an important need to better understand the contributing factors. Aim: We sought to analyze the prevalence of maladaptive behavior and its association with intellectual functioning, adaptive skills, language skills, and social communication in a population of adults with deafness and special needs. Methods: Participants were 61 individuals from three therapeutic living communities established for people with deafness and special needs. The participants had a mean age of 54.7 years, 64% were male. Intellectual functioning was measured with two versions of the Snijders–Oomen Non-verbal Intelligence Scale. The Vineland-II Scales were used to assess adaptive and maladaptive behavior. Language skills were measured with instruments specifically adapted for this population, including the Reynell Developmental Language Comprehension Scale, the comprehension scale of the Child Development Inventory, and the Profile of Multiple Language Proficiencies. Due to high correlations between instruments, a composite language score was used. A specific questionnaire to measure social communication in adults with intellectual disabilities was also utilized. Results: The mean nonverbal developmental reference age was 6.5 years, whereas the equivalent for the language measures was about 3.5 years. The prevalence rate of elevated maladaptive behavior was 41% (v-scale score >=18) and 18% of the participants had a clinically significant score (v-scale score >=21). Regression analyses showed that only language and social communication skills were significantly associated with maladaptive behaviour, while intellectual functioning and adaptive skills were not. Conclusion: These findings emphasize the importance of the constant promotion of communicative skills, as those people with better language and social communication skills demonstrate lower levels of maladaptive behavior.